Universally optimal designs under interference models with and without block effects. Issue 3 (1st February 2017) - Filipiak, Katarzyna; Markiewicz, Augustyn
ABSTRACT: The concept of neighbor designs was introduced and defined by Rees (1967 ) along with giving some methods of their construction. Henceforth, many methods of construction of neighbor designs as well as of their generalizations are available in the literature. However, there are only few results on their optimality. Therefore, the purpose of this article is to give an overview of study on this problem. Recent results on optimality of specified neighbor balanced designs under various interference models with block effects are presented and then these results are compared with respective models where block effects are not significant.